Effects of Different Dietary Levels of Two Types of Olive Pulp and Exogenous Enzyme Supplementation on the Gastrointestinal tract size, Immunology and Hematology of Broilers - Sayehban,P (2015)
ABSTRACT The effects of the dietary inclusion of olive pulp (OP) and the supplementation of a commercial enzyme blend (ENZ) on the gastrointestinal tract (GIT) size, and immune and hematological parameters were evaluated. In total, 600 one-day-old Ross 308 male broiler chicks were divided into 6 treatments according to a completely randomized design, in a 2×2×2 factorial scheme, consisting of the dietary inclusion of two olive pulp levels (50 and 100 g/kg in diet), two pulp categories (processed and unprocessed), and the inclusion or not of an enzyme blend. On d 42, birds were euthanized and blood samples were collected, and lymphoid, hematologic, and GIT organs were measured. The inclusion of 100g/kg OP in the diets increased jejunum relative weight (J%) and jejunum length (p ≤ 0.05). Processed OP reduced jejunum weight and length, J%, and left cecum length, serum triglycerides and VLDL cholesterol levels (p ≤ 0.05). Enzyme supplementation did affect any of the studied parameters (p>0.05). The OP inclusion improved the GIT size, while processed OP reduced GIT measurements and serum lipid levels.